The role of G-density in switch region repeats for immunoglobulin class switch recombination - Zhang, Zheng Z.; Pannunzio, Nicholas R.; Hsieh, Chih-Lin; Yu, Kefei; Lieber, Michael R. (Nucleic acids research, 2014)
The boundaries of R-loops are well-documented at immunoglobulin heavy chain loci in mammalian B cells. Within primary B cells or B cell lines, the upstream boundaries of R-loops typically begin early in the repetitive portion of the switch regions. Most R-loops terminate within the switch repetitive zone, but the remainder can extend a few hundred base pairs further, where G-density on the non-template DNA strand gradually drops to the genome average. Whether the G-density determines how far the R-loops extend is an important question. We previously studied the role of G-clusters in initiating R-loop formation, but we did not examine the role of G-density in permitting the elongation of the R-loop, after it had initiated. Here, we vary the G-density of different portions of the switch region in a murine B cell line. We find that both class switch recombination (CSR) and R-loop formation decrease significantly when the overall G-density is reduced from 46% to 29%. Short 50 bp insertions with low G-density within switch regions do not appear to affect either CSR or R-loop elongation, whereas a longer (150 bp) insertion impairs both. These results demonstrate that G-density is an important determinant of the length over which mammalian genomic R-loops extend.